A family in the structure of values of young people - Artur А. Rean (Rossijskij psihologičeskij žurnal., 2017)
Despite the fact that a family is extremely significant in the system of values of young people, the number of divorces is increasing in this population group. The analysis establishes that young people need to be prepared for family life. The paper presents the results of a large-scale empirical study conducted in eight regions in Russia’s various federal districts. The study involved over 7000 respondents from two-parent and one-parent families, as well as families with up to two children and large families; they were inhabitants of Russian large and small cities and villages. The findings of the study revealed that (a) a family led in the structure of young people’s life values. (b) Most respondents believed that a family was a precondition for happiness. (c) Most respondents noted that one should be prepared for family life. (d) Only a third of respondents believed that a school course in family issues could solve this problem. (e) Most respondents noted that their parent families failed to be role models. (f) Young people’s reproductive attitudes towards having two or three children did not correspond to modern real demographic statistics. (g) More than half of the respondents approved civil marriages. (h) Young people were less tolerant towards births outside of marriage. (i) Mothers had greater influence on young people in their development. (j) The generalized portraits of mothers and fathers were entirely positive (without any negative characteristics). (k) The most popular common qualities of both mothers and fathers were the following: kind, dependable, caring, responsible, domestic, and clever.